2022
DOI: 10.1073/pnas.2116967119
|View full text |Cite
|
Sign up to set email alerts
|

Music of infant-directed singing entrains infants’ social visual behavior

Abstract: Infant-directed singing is a culturally universal musical phenomenon known to promote the bonding of infants and caregivers. Entrainment is a widely observed physical phenomenon by which diverse physical systems adjust rhythmic activity through interaction. Here we show that the simple act of infant-directed singing entrains infant social visual behavior on subsecond timescales, increasing infants’ looking to the eyes of a singing caregiver: as early as 2 months of age, and doubling in strength by 6 months, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 70 publications
3
36
0
Order By: Relevance
“…Bahrick & Lickliter., 2000; Bahrick et al., 2004). Of course, in the youngest infants in the sample (<∼6 months), infants preferentially looked at the eyes in both speech and song contexts, consistent with the importance of eye‐looking for social and emotional regulation (Farroni et al., 2002; Jones & Klin, 2013; Lense et al., 2022); however, even at these early age points, the preference for eyes was attenuated during song. Earlier and more rapid increases in mouth‐looking in song may also reflect more efficient processing of the sung signal, perhaps in part due to these multimodal, ID characteristics (e.g., slower tempo, increased AVS; Singh et al., 2009; Song et al., 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Bahrick & Lickliter., 2000; Bahrick et al., 2004). Of course, in the youngest infants in the sample (<∼6 months), infants preferentially looked at the eyes in both speech and song contexts, consistent with the importance of eye‐looking for social and emotional regulation (Farroni et al., 2002; Jones & Klin, 2013; Lense et al., 2022); however, even at these early age points, the preference for eyes was attenuated during song. Earlier and more rapid increases in mouth‐looking in song may also reflect more efficient processing of the sung signal, perhaps in part due to these multimodal, ID characteristics (e.g., slower tempo, increased AVS; Singh et al., 2009; Song et al., 2010).…”
Section: Discussionsupporting
confidence: 57%
“…The predictable rhythmic patterns, melodies, and lyrics of the song books may help dyads track how the song unfolds over time and contribute to increased attention and behavior modulation (Hardy & LaGasse, 2013;Miller et al, 2013). Song activities may also support attention and engagement because they naturally involve predictable and salient multimodal cues (e.g., head movements, gestures) that are coordinated with the rhythm of the song (Lense & Jones, 2016;Trehub et al, 2016) and because song activities modulate emotion and arousal levels in both partners in the dyad Fancourt & Perkins, 2018;Shenfield et al, 2003). These attributes of the song books might have made them more accessible for children and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…However, infant gaze behavior during the playsong was neither associated with their neural tracking nor rhythmic movements in that condition. Instead, we found that neural tracking of lullabies was weaker when infants looked away from mothers' faces and bodies, suggesting that neural tracking is related to infants' attention towards the face (Lense et al, 2022). To disentangle factors underlying infants' neural tracking during ID songs, future studies thus need to include more in-depth analyses of the accompanying sensorimotor synchronization processes, including caregivers' movements (e.g., rocking, playful gestures, etc.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Cirelli et al (2016) showed that 7-month-old infants’ brains track the beat and meter of rhythmic patterns. At the behavioral level, infants coordinate their gaze with the beat of ID singing as early as 2 months of age (Lense et al, 2022), and adjust their movements to the tempo of the music they hear by 6 months (Ilari, 2015; Zentner & Eerola, 2010). This evidence suggests that young infants are not only receptive to but often also coordinate with music and other rhythmic sounds within their abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation